Monitoring Trends of Land Use and Land Cover Changes in Rajang River Basin - Oad, V.K. (Institute of Electrical and Electronics Engineers Inc., 2020)
In this study, the spatiotemporal changes in land use and land cover (LULC) were evaluated from 1992 to 2015 for the Rajang River Basin (RRB) located in Sarawak State of Malaysia. The changes in water bodies, cropped lands, and forests were assessed based on the available remotely sensed satellite data. Supervised classification with the MaximumLikelihood-Algorithm technique was adopted for monitoring the LULC changes using Geographic Information System (GIS) and ERDAS Imagine tools. The results revealed increasing trend of agricultural areas, mosaic natural vegetation and water bodies, while other classified areas such as tree broadleaved evergreen closed to open, tree cover flooded fresh or brackish water followed decreasing trend. More importantly, tree broadleaved evergreen closed to open and tree cover flooded fresh or brackish water showed drastic changes over the last decade. These LULC changes could be attributed to rapid economic development, disproportionate urbanization, population growth, and climate change. If unchecked, these changes might lead to a wide range of environmental impacts including aquatic and terrestrial habitat disruption. Â© 2020 IEEE.